Podoplanin expression in malignant ovarian cancer - Marzec-Kotarska, Barbara; Kotarski, Józef; Cybulski, Marek; Antosz, Halina; Kocki, Janusz; Bednarek, Wiesława (Menopause Review/Przegląd Menopauzalny, 2011)
Introduction: Ovarian cancer is mostly diagnosed in postmenopausal women. The hormonal microenviron- ment of ovarian tumour development in pre- and postmenopausal women is different. The environment may influence the molecular basis of ovarian cancer. Podoplanin is a proven marker of lymphangiogenesis and is engaged in tumour progression and metastasis. Objectives: The aim of our study was to assess podoplanin expression at the mRNA level in ovarian serous and mucinous adenocarcinoma. Material and methods : mRNA expression of podoplanin was assessed in 42 ovarian cancer patients by means of real-time PCR. Results : Podoplanin was expressed at the mRNA level in all ovarian cancer patients. It was significantly lower (p < 0.001) in cancer tissues (RQ = 4.46) than in healthy control (RQ = 13.03). No significant differences were found in podoplanin expression either between pre- and postmenopausal women or in relation to FIGO and grading Conclusion : Decreased podoplanin expression is characteristic for serous and mucinous ovarian adenocarcinoma.